2002
DOI: 10.1007/bf03344008
|View full text |Cite
|
Sign up to set email alerts
|

The low dose dexamethasone suppression test: Effect of time of administration and dose

Abstract: The dexamethasone suppression test (DST) is used to determine the sensitivity of the hypothalamic-pituitary-adrenal axis (HPA-axis) to negative feedback. Dexamethasone is usually administered at 23:00 h or at midnight but this is often not convenient. The aim of this study was to determine whether the administration of dexamethasone at 21:00 h as compared to 23:00 h would alter the degree to which 08:00 h plasma cortisol was suppressed the following morning. Three healthy males (mean+/-SE: 32+/-7 yr) and 3 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Frailty is a dynamic state affecting an individual who experiences accelerated decline in several domains of homeostatic mechanisms (physical, psychological, and social) 12 . One previous study showed the predictive value of HOMA-IR on habitual gait speed, one of the domains of frailty 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Frailty is a dynamic state affecting an individual who experiences accelerated decline in several domains of homeostatic mechanisms (physical, psychological, and social) 12 . One previous study showed the predictive value of HOMA-IR on habitual gait speed, one of the domains of frailty 13 .…”
Section: Discussionmentioning
confidence: 99%
“…This occurred in the face of higher circulating cortisol levels prior to dexamethasone treatment compared with the same time on the previous day, which was likely a result of repeated handling (Sapolsky et al, 2000;Bennett et al, 2012). In bottlenose dolphins, humans and horses, a similar or slightly higher mass-specific dose of dexamethasone causes suppression of circulating cortisol to 0-30% of initial levels within 24h and has observable effects on food-seeking behaviour (Barton et al, 2002;Froin et al, 1998;Reidarson and McBain, 1999). The rapid, dramatic and sustained impact of the dose of dexamethasone used here indicates that it mimicked the negative feedback effect of high levels of endogenous cortisol over a period of 1-2days.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, some of the most widely studied biomarkers of aging are inflammatory mediators and coagulation factors, such as IL-6, TNF-α, CRP and D-dimer. Inflammatory and coagulation markers are easily measured, increase with age, and are associated with functional decline and increased mortality in community-dwelling older adults [8, 12, 13, 25, 3741]. …”
Section: Discussionmentioning
confidence: 99%